2008
DOI: 10.1097/mot.0b013e328308b2d9
|View full text |Cite
|
Sign up to set email alerts
|

In defense of a regulated system of compensation for living donation

Abstract: We suggest that the potential advantages of a regulated system of compensation for donation far outweigh any potential disadvantages. It is time to advocate for a change in the law so that trials can be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…While education, paired exchange and expanded criteria donors have helped slightly, the organ demand still greatly exceeds supply. Within this milieu, proposals to introduce financial compensation for organ procurement from living and deceased donors have garnered increased attention and debate (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…While education, paired exchange and expanded criteria donors have helped slightly, the organ demand still greatly exceeds supply. Within this milieu, proposals to introduce financial compensation for organ procurement from living and deceased donors have garnered increased attention and debate (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Some, including us, have suggested that a regulated system of incentives might increase donation and alleviate the crisis (1,2). Others, championed by Chapman, Danovitch, Padilla and Delmonico, have passionately opposed this option (3-6).…”
Section: To the Editormentioning
confidence: 99%
“…That additional bit of deliberation is morally good for both the patient's family (the "donative sources") and any potential recipient of such a gift. That additional element of process might assuage any misgivings or guilt that might accompany the giving, or receipt, of an organ because it helps ensure that the donative act was neither coerced nor forced but rather one of informed altruism, a standard for which we should strive, particularly given the recent encroachment of the market into the donative space [28].…”
Section: Temperancementioning
confidence: 99%